When Rabbis Abuse: Power, Gender, and Status in the Dynamics of Sexual Abuse in Jewish Culture - Sztokman, Elana (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2024)
This book excerpt is the introductory chapter of Elena Sztokman’s When Rabbis Abuse: Power, Gender, and Status in the Dynamics of Sexual Abuse in Jewish Culture (2022). The chapter features a prologue, along with discussions such as the background of the topic and how prevalent sexual abuse is in the Jewish community, what are the dynamics of sexual abuse in the Jewish community? and identifying rabbis who committed sexual abuse.